Bimbingan dan Konseling Komprehensif Berbasis Nilai Budaya Lokal untuk Meningkatkan Adaptabilitas Karir dan Kecerdasan Emosional: Tinjauan Literatur Sistematis - Wulan Muin, Siti Rahma; Prasetya, Akhmad Fajar; Santosa, Hardi; Kumara, Agus Ria (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the role of comprehensive Guidance and Counseling (BK) based on local cultural values in improving career adaptability and emotional intelligence of students and students. The background of this research is based on the importance of students' readiness to face the demands of the dynamic world of work, as well as overcoming career anxiety and adaptability limitations that often arise in the digital era and disruption 4.0. The research uses a qualitative approach with a systematic literature study method, including the collection, reading, and analysis of 22 scientific articles, journals, and trusted books published between 2015–2025. The literature selection process follows the PRISMA model, starting from title and abstract screening, full-text screening, to article quality validation. The results of the study showed that comprehensive BK was effective in improving career adaptability and emotional intelligence through structured strategies, diverse counseling interventions (CBT, Pictorial Narrative, KIPAS Model, and digital services), as well as social support and counselor competence. The integration of local cultural values has been proven to strengthen students' identities while increasing career readiness. This study emphasizes that the development of comprehensive BK based on modern strategies and local culture is an effective solution to support the career readiness, adaptability, and psychological well-being of students.